Increasing Knowledge of HIV/AIDS in Adolescents using Video-Blogging - Intan Manisha Natalia; Sondang Ratnauli Sianturi; Wilhelmus Hary Susilo (Media Keperawatan Indonesia, 2021)
Video-Blogging (Vlog) is one of the media that is of interest to today's millennial youth because it contains audiovisuals and digital images so that it can attract the attention of teenagers. One of the health promotion strategies using Vlog is to increase adolescent knowledge about HIV / AIDS. This study aims to determine the effectiveness of health promotion using vlog media on the level of adolescent knowledge. This research is a quantitative study with a quasi-experimental, one group pre and post-test design without a control group and a descriptive correlation. The sampling techniques is using a purposive sampling technique as many as 64 students. Statistical test using Wilcoxon and Kendal's tau.  The univariate results in this study were 45.3% male and 54.7% female, 43.8% information media from Radio/Tv / Internet. The results of the bivariate analysis were differences before and after health promotion (p-value = 0.000), but there was no significant relationship between vlog media and changes in knowledge levels (p-value = 0.249). The strategy to increase knowledge about HIV / AIDS in adolescents needs to be modified according to several other types of media so that the effectiveness of each media can be seen clearly.